2022
DOI: 10.3390/cells11010156
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Proteolytic Processing of N-Cadherin as a Marker of Human Fibrotic Disease

Abstract: Prior research has implicated the involvement of cell adhesion molecule N-cadherin in tissue fibrosis and remodeling. We hypothesize that anomalies in N-cadherin protein processing are involved in pathological fibrosis. Diseased tissues associated with fibrosis of the heart, lung, and liver were probed for the precursor form of N-cadherin, pro-N-cadherin (PNC), by immunohistochemistry and compared to healthy tissues. Myofibroblast cell lines were analyzed for cell surface pro-N-cadherin by flow cytometry and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(75 reference statements)
1
11
0
Order By: Relevance
“…The adhesive capacity of cadherins relies on the removal of the prodomain because cleavage of the precursor peptide is required for the maturation of N-cadherin. The endogenous cleavage site mutation may not affect the N-cadherin targeting the plasma membrane but may disturb the interaction between N-cadherins to form homodimers ( 33 , 34 ). Previous studies have shown that endogenous protease digestion depends on the recognition site (Arg-X 1 -Lys-Arg-X 2 -Trp, i.e., R-X 1 -K-R-X 2 -W polypeptide) ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive capacity of cadherins relies on the removal of the prodomain because cleavage of the precursor peptide is required for the maturation of N-cadherin. The endogenous cleavage site mutation may not affect the N-cadherin targeting the plasma membrane but may disturb the interaction between N-cadherins to form homodimers ( 33 , 34 ). Previous studies have shown that endogenous protease digestion depends on the recognition site (Arg-X 1 -Lys-Arg-X 2 -Trp, i.e., R-X 1 -K-R-X 2 -W polypeptide) ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, upregulated N-cadherin expression in alveolar type II cells has been observed in IPF patients and is considered a potential prognostic indicator based on N-cadherin and Ki-67 expression correlation with histological disease activity (26). Recently, Ferrell et al also demonstrated that retention of the N-cadherin prodomain at the cell surface is a potential biomarker of pathological myofibroblasts and is linked with tissues of the heart, lung and liver fibrosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the N-cadherin prodomain at the cell surface is a potential biomarker of pathological myofibroblasts and fibrosis in many tissues [ 24 ], and that TGF-β derived from colon cancer cells could induce N-cadherin expression, which consequently promoted invasion of myofibroblasts [ 23 ]. In association with cell motility and invasion, N-cadherin molecules were complexed with β-actin and the α-SMA cytoskeleton, and the findings suggested that N-cadherin might stimulate invasion by forming adherens junctions linked to the cytoskeleton [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human fibroblasts have been proven to express N-cadherin [ 22 ], and TGF-β can induce the expression of N-cadherin, which is involved in myofibroblast invasion and migration [ 23 ]. Specifically, pathologic proteolytic processing of N-cadherin has been identified as a marker of human fibrotic diseases [ 24 ]. Since TGF-β has diverse fibrotic effects, this growth factor has become a potential therapeutic target for skin fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%